2014
DOI: 10.1186/1752-4458-8-11
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness of Lithuanian general practitioners to provide mental healthcare services: a cross-sectional survey

Abstract: BackgroundA large unmet need for mental healthcare in Lithuania is partially attributable to a lack of primary care providers with skills in this area. The aim of this study was to assess general practitioners’ (GPs) experience in mental healthcare and their perceptions about how to increase their involvement in the field.MethodsIn this cross-sectional study, a 41-item questionnaire was distributed to a random sample of 797 Lithuanian GPs in order to investigate current practices in their provision of mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Studies have indicated the need for supervision and training of PHCT for the adequate care of patients in psychological distress 16 , 17 , 22 , 27 . The matrix support would be able to increase the resolutiveness and the effectiveness of the actions, acting together with the PHCT in their territory, subsidizing group activities, health promotion actions, and training of PHC professionals 7 , 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated the need for supervision and training of PHCT for the adequate care of patients in psychological distress 16 , 17 , 22 , 27 . The matrix support would be able to increase the resolutiveness and the effectiveness of the actions, acting together with the PHCT in their territory, subsidizing group activities, health promotion actions, and training of PHC professionals 7 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…An important factor for the treatment of persons in mental distress by the PHC is the qualification of professionals. These professionals have reported feeling unprepared for such care 13 , 16 , 17 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The formal network of the health and social care systems is complicated and depends on the specific different legal frameworks, policies and separate financing [9]. Navigation through this network is challenging to the patients, their caregivers, and to health care professionals [10]. Eventually, teamwork and collaboration between the health and social care sectors become challenging: investigation of the cross-sector service delivery in health and social care highlights the necessity for delineating existing facilitators and barriers in cross-sector collaboration and use them to shape a common vision of care across different sectors [11].…”
Section: Introductionmentioning
confidence: 99%
“…Fragmentation of health and social care is also an issue in Lithuania where there is a lack of collaboration between family physicians and social workers [10]. It is especially problematic in the context of financial strain—spending’s on social protection per person in Lithuania reach nearly half of the EU average [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation